Membrane-Interactive Compounds From Pistacia lentiscus L. Thwart Pseudomonas aeruginosa Virulence - Tahrioui, Ali; Ortiz, Sergio; Azuama, Onyedikachi Cecil; Bouffartigues, Emeline; Benalia, Nabiha; Tortuel, Damien; Maillot, Olivier; Chemat, Smain; Kritsanida, Marina; Feuilloley, Marc; Orange, Nicole; Michel, Sylvie; et al. (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa is capable to deploy a collection of virulence factors that are not only essential for host infection and persistence, but also to escape from the host immune system and to become more resistant to drug therapies. Thus, developing anti-virulence agents that may directly counteract with specific virulence factors or disturb higher regulatory pathways controlling the production of virulence armories are urgently needed. In this regard, this study reports that Pistacia lentiscus L. fruit cyclohexane extract (PLFE1) thwarts P. aeruginosa virulence by targeting mainly the pyocyanin pigment production by interfering with 4-hydroxy-2-alkylquinolines molecules production. Importantly, the anti-virulence activity of PLFE1 appears to be associated with membrane homeostasis alteration through the modulation of SigX, an extracytoplasmic function sigma factor involved in cell wall stress response. A thorough chemical analysis of PLFE1 allowed us to identify the ginkgolic acid (C17:1) and hydroginkgolic acid (C15:0) as the main bioactive membrane-interactive compounds responsible for the observed increased membrane stiffness and anti-virulence activity against P. aeruginosa. This study delivers a promising perspective for the potential future use of PLFE1 or ginkgolic acid molecules as an adjuvant therapy to fight against P. aeruginosa infections.